Seroprevalence and factors associated with toxoplasmosis among pregnant women attending antenatal care clinic at a tertiary teaching hospital in Uganda: a cross-sectional study - Rukamba, Jean de Dieu; Hakizimana, Theoneste; Ishimwe, Marie Pascaline Sabine; Adoch, Christine Olwedo; Pius, Theophilus; Baluku, Asanairi; Musiime, James Nabaasa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Toxoplasmosis is an infection caused by a parasite called Toxoplasma gondii and is progressively increasing in pregnancy mainly with age and if left undiagnosed and untreated, can result into several adverse pregnancy outcomes. In Uganda, there is a paucity of information about toxoplasmosis in pregnancy. This study aimed to determine the seroprevalence and factors associated with toxoplasmosis among pregnant women attending antenatal care clinic at a Tertiary hospital in Uganda. Methods: This was a cross-sectional study carried out from July 2022 to October 2022. 165 pregnant women were consecutively enrolled. Data gathered for analysis were collected using a pre-tested structured questionnaire. Blood samples were taken and test of Toxoplasma gondii specific IgG and IGM was done using EUROIMMUN ELISA test kits as instructed by manufacturer. Data was analyzed using STATA version 14.2. A bivariate and multivariate analysis were used to show the association between the dependent and independent variables considering p≤0.05 at 95% confidence interval. Results: The overall seroprevalence of toxoplasmosis in pregnancy was 16.4%. Age >35 years old (aOR: 8.36; 95% CI: 1.809-38.71; p=0.007), having contact with cats (aOR: 3.55; 95% CI: 1.258-10.01; p=0.017), drinking untreated water (aOR=4.08; 95% CI:1.237-13.46; p=0.021) and HIV status (aOR=8.91; 95% CI: 1.419-56.03; p=0.020) were independently associated with toxoplasmosis infection. Conclusions: The overall seroprevalence of toxoplasmosis in pregnancy was low as compared to the global seroprevalence. There is a need to educate pregnant women about the transmission routes and preventive measures of toxoplasmosis at antenatal care.